Inappropriate Circumcision: Referrals by General Practitioners (Journal of Paediatric Surgeons of Bangladesh, 2015)
A large proportion of general practitioners have difficulty in discriminating between a true phimosis and a developmentally non-retractile foreskin. This diagnostic inaccuracy was greatest when the referring doctor did not examine the patient and inappropriately refer the patient to a pediatric surgeon for circumcision due to fear of obstructed voiding. From July 2005 to April 2007 total 33 boys with physiological phimosis were assessed in BSMMU. Among them 20 cases were without ballooning and 13 cases with ballooning. All the boys had upper tract and bladder USG followed by uroflowmetry and USG to determine post-void residual urine volume. Data were compared between boys with and without ballooning of foreskin. In all 33 boys with physiological phimosis completed uroflowmetry and USG. Ballooning of the foreskin was present in 13 boys (mean age-22.08 months range from 18 to 25 months) and non ballooning were 20 (mean age-22.7 months range from 18 to 28 months). Upper tract USG and bladder wall thickness were normal in all boys. The mean Maximum flow rate (Q max) was not significantly different in boys with ballooning and those with non ballooning (mean 8.4ml/s maxi-10.3 mini-6.7-) vs (8.5 ml/ s, maxi-10.7,mini -6.7). In addition all Qmax values were within normal range. The two groups had comparable mean PVR (0 .92 ml SD-0.9, range -0 to7) vs (.85 ml SD-0.8 range 0 to 8). The non-invasive assessment of voiding efficiency in boys with physiological phimosis with or without ballooning of foreskin showed no evidence of obstructed voiding). In conclusion physicians should be educated on the conservative management and care of thel foreskin and be able to distinguish between physiological phimosis and balanitis xerotica obliterans in order to decrease inappropriate circumcision referrals.2, 3J. Paediatr. Surg. Bangladesh 4(1): 19-23, 2013 (January)